2017
DOI: 10.1007/s10653-017-9911-z
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency status in the WHO Eastern Mediterranean Region: a systematic review

Abstract: Iodine deficiency is a global public health issue because iodine plays a major role in the thyroid hormone synthesis and is essential for normal neurological development. This review summarizes the publications on iodine status in the WHO Eastern Mediterranean Region (EMR) countries. All related studies available in main national and international databases were systematically searched using some specific keywords to find article published between 1909 and 2015. The prevention of iodine deficiency disorders (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…Several surveys among Egyptian children revealed that there is mild iodine deficiency in 60.6% of children and moderate to severe deficiency in 31.3%; the prevalence of goiter is higher in some regions such as South Sinai. 18 This is a community-based study that was conducted to determine the knowledge status, factors associated with knowledge and the utilization practices of women on iodized salt in Fayoum governorate. The use of iodized salt by individuals and households is the major approach in the control of iodine deficiency diseases worldwide 19 so; strengthening salt iodization program improving its monitoring is a crucial step to eradicate the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys among Egyptian children revealed that there is mild iodine deficiency in 60.6% of children and moderate to severe deficiency in 31.3%; the prevalence of goiter is higher in some regions such as South Sinai. 18 This is a community-based study that was conducted to determine the knowledge status, factors associated with knowledge and the utilization practices of women on iodized salt in Fayoum governorate. The use of iodized salt by individuals and households is the major approach in the control of iodine deficiency diseases worldwide 19 so; strengthening salt iodization program improving its monitoring is a crucial step to eradicate the problem.…”
Section: Discussionmentioning
confidence: 99%
“…The status of nutritional iodine could be influenced by numerous factors in reproductive age women [36][37][38]. Herein, the risk of developing iodine deficiency was highest during the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The United Arab Emirates (UAE) is classified as an area with minimal iodine-deficiency with rate of households using iodized salt around 6% and a median urinary iodine excretion of 100 μg/l. Therefore, a high prevalence of thyroid malignancy is not unexpected [4][5][6][7]. Thyroid malignancy is the most common endocrine malignancy in the UAE, and papillary thyroid cancer is the most common type of thyroid cancer [4].…”
Section: Introductionmentioning
confidence: 99%